Jurassic magmatism and Au-Ag mineralization in the Deseado Massif (Patagonia Argentina) : Lead and sulfur isotopic studies - Moreira, Pilar (2005)
Lead isotope analyses of volcanic rocks and hydrothermal minerals and sulfide isotope analyses of sulfurs from Au-Ag La Josefina prospect (Deseado Massif geological province, Argentina) are reported. Lead isotope ratios for sphalerite and pyrite have mean values of 18.48, 15.69 and 38.61 for 206Pb/204Pb, 207Pb/204Pb and 208Pb/204Pb, respectively, and are similar to Pb isotope ratios for the Jurassic volcanic rocks of Bajo Pobre and Chon Aike Formations. δ34S‰ suggesting that the sulfur at La Josefina was primarily of magmatic origin. These results are interpreted to indicate that the Jurassic volcanic rocks are closely related with low sulfidation Au-Ag occurrences.